Automatic Modelling of the Lower Bodies of Young Females Based on Digital Photographs (Journal of Fiber Bioengineering and Informatics, 2014)
The determination of curve generation rules for the body features is the lynchpin in the creation ofcomputer generated three dimensional (3D) lower body human mannequins. In this paper, methodsto determine the characteristic features of the curves, such as the waist curve, abdomen curve andhip curve were analyzed as a precursor to creating female lower body 3D mannequins. Methods togenerate the profile curves for the different body features were devised by adding insertion points ontothe curves. The relationships between the coordinates of the insertion points and body measurementdata were analyzed using SPSS software and rules for the generation of curves for each of the featuredparts were determined. Subsequently these were used to provide the basis for the creation of a femalelower body 3D mannequin, which can be useful for the further development of clothing e-commerce.The modelling system was developed by automatically extracting anthropometric data from a non-contact 2D anthropometry system (photographs) and used to generate human models according to theirdifferent body features. The system can facilitate the interactive design of different fashion styles andthe automatic generation of garment patterns.
Keywords: Computer Aided Design (CAD); Characteristic Position Curves; Mannequin Modelling; Point cloud Data; Anthropometry